Impacts of Heat and Mass Transfer on Magneto Hydrodynamic Peristaltic Flow Having Temperature-dependent Properties in an Inclined Channel Through Porous Media - Kareem, Rabiha S.; Abdulhadi, Ahmed M. (Iraqi Journal of Science, 2020)
In this paper, we study the impacts of variable viscosity , heat and mass transfer on magneto hydrodynamic (MHD) peristaltic flow in a asymmetric tapered inclined channel with porous medium . The viscosity is considered as a function of temperature. The slip conditions at the walls were taken into consideration. SmallReynolds number and the long wavelength approximations were used to simplify the governing equations. A comparison between the two velocities in cases of slip and no-slip was plotted. It was observed that the behavior of the velocity differed in the two applied models for some parameters. Mathematica software was used to estimate the exact solutions of temperature and concentration profiles. The resolution of the equations to the momentum was based on the perturbation method to find the axial velocity, pressure gradient and trapping phenomenon. The influences of the various flow parameters of the problem on these distributions were debated and proved graphically by figures.